3D-speckle-tracking echocardiography correlates with cardiovascular magnetic resonance imaging diagnosis of acute myocarditis – An observational study. (August 2022) - Goody, Philip Roger; Zimmer, Sebastian; Öztürk, Can; Zimmer, Angela; Kreuz, Jens; Becher, Marc Ulrich; Isaak, Alexander; Luetkens, Julian; Sugiura, Atsushi; Jansen, Felix; Nickenig, Georg; Hammerstingl, Christoph; et al.
Highlights: Regional changes in myocardial texture (as diagnosed by CMR) were significantly associated with regional impairment of circumferential, longitudinal, and radial strain, as well as regional 3D displacement and total 3D strain. 3D and 2D global longitudinal strain (GLS) showed higher diagnostic performance than well-known parameters associated with myocarditis, such as LVEF and LVEDV in our patient collective. 3D-speckle-tracking echocardiography offers a promising diagnostic tool in the diagnosis of myocarditis. Abstract: Background: The diagnostic importance of three-dimensional (3D) speckle-tracking strain-imaging echocardiography in patients with acute myocarditis remains unclear. The aim of this study was to test the diagnostic performance of 3D-speckle-tracking echocardiography compared to CMR (cardiovascular magnetic resonance imaging) for the diagnosis of acute myocarditis. Methods and results: 45 patients with clinically suspected myocarditis were enrolled in our study (29% female, mean age: 43.9 ± 16.3 years, peak troponin I level: 1.38 ± 3.51 ng/ml). 3D full-volume echocardiographic images were obtained and offline 2D as well as 3D speckle-tracking analysis of regional and global LV deformation was performed. All patients received CMR scans and myocarditis was diagnosed in 29 subjects based on original Lake-Louise criteria. The 16 patients, in whom myocarditis was excluded by CMR, served as controls. Regional changes in myocardial texture (diagnosed by CMR) were significantly associated with regional impairment of circumferential, longitudinal, and radial strain, as well as regional 3D displacement and total 3D strain. Interestingly, the 2D and 3D global longitudinal strain (GLS) showed higher diagnostic performance than well-known parameters associated with myocarditis, such as LVEF (as obtained by echocardiography and CMR) and LVEDV (as obtained by CMR). Conclusions: In this study, we examined the use of 3D-speckle-tracking echocardiography in patients with acute myocarditis. Global longitudinal strain was significantly impaired in patients with acute myocarditis and correlated with CMR findings. Therefore, 3D echocardiography could become a useful diagnostic tool in the primary diagnosis of myocarditis.